To manipulate the equation \( y = 5x - 11 \) in terms of \( x \), we will solve for \( x \).
Starting with the equation: \[ y = 5x - 11 \]
Add 11 to both sides: \[ y + 11 = 5x \]
Now, divide both sides by 5: \[ x = \frac{y + 11}{5} \]
This equation can also be expressed as: \[ x = \frac{y}{5} + \frac{11}{5} \]
Now let's compare this with the options given:
A. \( x = \frac{y}{11} - 5 \)
B. \( x = \frac{y + 11}{5} \)
C. \( y - \frac{11}{5} \) (This doesn't represent \( x \))
D. \( x = \frac{y}{5} + 11 \) (This is incorrect; it doesn't match our derived equation.)
The correct answer is B. \( x = \frac{y + 11}{5} \).